Chloroform Fraction of Centratherum anthelminticum (L.) Seed Inhibits Tumor Necrosis Factor Alpha and Exhibits Pleotropic Bioactivities: Inhibitory Role in Human Tumor Cells - Arya, A.; Achoui, M.; Cheah, S. C.; Abdelwahab, S. I.; Narrima, P.; Mohan, S.; Mustafa, Mohd Rais; Mohd, M. A. (Hindawi, 2011)
We investigated the antioxidant potential, cytotoxic effect, and TNF-α inhibition activity with NF-κB activation response in a chloroformfraction of Centratherum anthelminticum seeds (CACF). The antioxidant property of CACF was evaluated with DPPH, ORAC, and FRAP assays, which demonstrated significant antioxidant activity. The cytotoxicity of CACF was tested using theMTT assay; CACF effective inhibitory concentrations (IC50) for A549, PC-3, MCF-7, and WRL-68 cells were 31.42 ± 5.4, 22.61 ± 1.7, 8.1±0.9, and 54.93±8.3 μg/mL, respectively. CACF effectively and dose-dependently inhibited TNF-α release, in vitro and in vivo. CACF inhibited TNF-α secretion in stimulated RAW264.7macrophage supernatants with an IC50 of 0.012 μg/mL, without affecting their viability; the highest dose tested reduced serum TNF-α by 61. Acute toxicity testing in rats revealed that CACF was nontoxic at all doses tested.Matching the cytotoxic activity towards a mechanistic approach, CACF dose-dependently exhibited in vitro inhibitory effects against the activation of NF-κB translocation in MCF-7 cells. Preliminary phytochemical screening with GC/MS analysis detected 22 compounds in CACF, of which morpholinoethyl isothiocyanate was the most abundant (29.04). The study reveals the potential of CACF in the treatment of breast cancer and in oxidative stress conditions with associated inflammatory responses.